Golden rage. Vol. 1 - Williams, Chrissy (Golden Rage, 2023)
"Older women have been deemed useless to society and abandoned on a remote island, where they must fight to the death, whilst making friends and dessert. Welcome to GOLDEN RAGE: a not-too distant dystopia where BATTLE ROYALE meets THE GOLDEN GIRLS."--Provided by publisher.